The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.cub.2012.03.069
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization Recovery after Defective Sperm Cell Release in Arabidopsis

Abstract: In animal fertilization, multiple sperms typically arrive at an egg cell to "win the race" for fertilization. However, in flowering plants, only one of many pollen tubes, conveying plant sperm cells, usually arrives at each ovule that harbors an egg cell. Plant fertilization has thus been thought to depend on the fertility of a single pollen tube. Here we report a fertilization recovery phenomenon in flowering plants that actively rescues the failure of fertilization of the first mutant pollen tube by attracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
126
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(140 citation statements)
references
References 29 publications
8
126
0
Order By: Relevance
“…x 2 analysis was used to test for significant deviation from the expected ratio of 1:1 if there was no rescue of failed division (i.e., 50% tricellular and 50% bicellular pollen); **P < 0.01, ***P < 0.001. ns, not significant. In six observations of single gamete discharge, fertilization of the egg or central cell did not occur (Figures 6H to 6M; Supplemental Movie 1 and 2), similar to previous observations of mutant duo3 germ cells and gcs1/hap2 sperm cells (Kasahara et al, 2012). Given that daz1 daz2 double mutant gametes are not competent for fertilization, we monitored gamete differentiation by introducing markers for two DUO1 target genes, the male gamete-specific histone H3.3 variant HTR10/MGH3 (Okada et al, 2005) and the sperm plasma membrane protein GCS1/HAP2, which is required for gamete fusion (Mori et al, 2006;von Besser et al, 2006).…”
Section: Daz1/daz2-dependent Pathways Are Also Required For Gamete DIsupporting
confidence: 69%
See 2 more Smart Citations
“…x 2 analysis was used to test for significant deviation from the expected ratio of 1:1 if there was no rescue of failed division (i.e., 50% tricellular and 50% bicellular pollen); **P < 0.01, ***P < 0.001. ns, not significant. In six observations of single gamete discharge, fertilization of the egg or central cell did not occur (Figures 6H to 6M; Supplemental Movie 1 and 2), similar to previous observations of mutant duo3 germ cells and gcs1/hap2 sperm cells (Kasahara et al, 2012). Given that daz1 daz2 double mutant gametes are not competent for fertilization, we monitored gamete differentiation by introducing markers for two DUO1 target genes, the male gamete-specific histone H3.3 variant HTR10/MGH3 (Okada et al, 2005) and the sperm plasma membrane protein GCS1/HAP2, which is required for gamete fusion (Mori et al, 2006;von Besser et al, 2006).…”
Section: Daz1/daz2-dependent Pathways Are Also Required For Gamete DIsupporting
confidence: 69%
“…The frequency of unfertilized ovules was 41.8 and 34.9%, respectively, which is less than the 50% expected based on the 1:1 segregation of wild-type and mutant pollen ( Figure 6G). These data are consistent with the secondary fertilization of some ovules by wild-type pollen tubes after initial entry of a mutant pollen tube (Beale et al, 2012;Kasahara et al, 2012). To directly investigate fertilization, we used a semi-in vitro assay (Kasahara et al, 2012) to observe the fate of single daz1 daz2 gametes released into the embryo sac.…”
Section: Daz1/daz2-dependent Pathways Are Also Required For Gamete DIsupporting
confidence: 64%
See 1 more Smart Citation
“…The impaired degeneration of the remaining synergid in ap1g/+ might be a secondary effect due to the failure of pollen tube discharge (23,24). Although as a fertilization recovery strategy after defective sperm cell release, nondegenerating synergids keep sending out attractive signals for pollen tubes (26,38), no supernumerary pollen tubes were observed in ap1g/+ FGs likely due to reduced pollen tube guidance.…”
Section: Discussionmentioning
confidence: 98%
“…25 However, it has been reported that additional pollen tubes can invade the embryo sac [37][38][39] when the sperm cell-egg cell fusion and/or the sperm cell-central cell fusion does not progress successfully 40,41 . This suggests that the egg:sperm ratio can vary, and that penetration of extra pollen tubes into the embryo sac provides the opportunity for multiple sperm cells to fuse with an egg cell.…”
Section: Cmentioning
confidence: 99%